1/1*2+1/2*3+1/3*4+……+1/2012*20131/1*2=1-1/21/2*3=1/2-1/31/3*4=1/3-1/4同理1/2012*2013=1/2012-1/20131/1*2+1/2*3+1/3*4+……+1/2012*2013=1-1/2+1/2-1/3+1/3-1/4+……+1/2011-1/2012+1/2012-1/2013=1-1/2013=2012/2013
计算:1/1*2+1/2*3+1/3*4+……+1/2012*2013怎么做?
2个回答
相关问题
-
请计算1/(2√1+1√2)+1/(3√2+2√3)+∧+1/[(2013√2012)+(2012√2013)]
-
计算-1/1×2-1/2×3-1/3×4-...-1/2012×2013
-
计算1/2-1绝对值+1/3-1/2绝对值+1/4-1/3绝对值+……+1/2013-1/2012绝对值
-
计算(-1×1/2)+(-1/2*1/3)+...+(-1/2012*1/2013)
-
计算:1/2013+2/2013+3/2013...+2012/2013=
-
计算:(-1)+(+2)+(-3)+(+4)+……(-2011)+(+2012)+(-2013)+(+2014)=
-
计算:1+(-2)+3+(-4).+2011+(-2012)+2013+(-2014)
-
计算:1+(-2)+3+(-4).+2011+(-2012)+2013+(-2014)
-
0-2^3/(-4)^3-1/8+2013*(-1)^2012 怎么算
-
|1/2-1|+|1/3-1/2|+|1/4-1/3|+……+|1/2013-1/2012|